Analysis of Dimensions of Quality of Services Based on Assessment and Satisfaction of Patients of BPJS Rawat Inap RSUD Wamena - Batmomolin, Caspar (Journal for Research in Public Health, 2020)
Quality of hospital services is a factor that influences patient assessment and satisfaction. The lower the assessment and patient satisfaction, the lower the quality of hospital services. The purpose of this study was to analyze the dimensions of service quality based on the assessment and satisfaction of BPJS patients. The dimensions of service quality used in this study are the dimensions of Sower's quality including respect and caring, effectiveness and continuity, appropriateness, information, efficiency, meals, first impression, staff diversity. This study was conducted with a cross sectional design, with a sample of 60 people drawn from the population of patients inpatient care at Wamena Hospital by simple random sampling. Data collection is done by questionnaire. The results of the study were analyzed using Linear Regression. The results showed that the assessment and satisfaction of inpatients was the lowest in the quality efficiency dimension. Testing with Linear Regression shows there is an influence between the assessment of patient satisfaction, BPJS (p <0.05) in all dimensions of quality with the largest correlation coefficient (r = 0.925) on the quality dimension of Appropriateness. The conclusion that can be drawn is the assessment and satisfaction of patients is still low in most dimensions of service quality. But the quality dimension of Appropriateness has the biggest role in determining the quality of hospital services. In the Efficiency quality dimension, things that can be done to improve patient assessment and satisfaction include reviewing cost issues through cost control, cost production programs, cost containment and transparency of the cost system for BPJS patients